A Review on Some Wound Healing Plants Traditionally Used in Democratic Republic of the Congo - Michel Mongeke Mobale; Jean-Paul Koto-Te-Nyiwa Ngbolua; Antoine Mumba Djamba; Elodie Mubikayi Jeannine; Monizi Mawunu; Colette Masengo Ashande; Pius T. Mpiana (Budapest International Research in Exact Sciences (BirEx) Journal, 2023)
Plants have been used by humans as a primary source of care in medicine since ancient times. Currently, about 80% of the population in southern Africa uses traditional medicine to meet their primary healthcare needs. The aim of this study was to document the healing plants traditionally used in the Democratic Republic of Congo. A systematic analysis and review of the virtual and physical literature search was conducted on the research literature related to healing medicinal plants used in the Democratic Republic of Congo. The results of the study reveal a total of 53 medicinal plants distributed in 50 genera and 31 families used for healing human wounds. The most represented families are Asteraceae (7 species), Euphorbiaceae (5 species), Rubiaceae (5 species), and Lialliaceae (3 species). Concerning the species abundance, the most represented genera are Allium (2 species), Morinda (2 species), and Vernonia (2 species). Herbaceous (39.6%, 21 species), shrubs (32.1%, 17 species) and trees (20.8%, 11 species), lianas (5.7%, 3 species), shrubs (1.9%, 1 species) are the main morphological types documented. Moreover, leaves and barks are the plant organs most used in healing. Thus, the documented therapeutic use of these plants provides the first baseline data for the city, and unveils further avenues of research into pharmacological and conservation studies.